PERFORMANSI NILAI TAMBAH KEDELAI MENJADI TAHU DI KABUPATEN SAMBAS - Muhsina Muhsina; S. Masduki; A A. Sa’diyah (BUANA SAINS, 2012)
The added value of soybean in agribusiness system either in the form of small industries and medium sized businesses by using as a main raw material, of as tofu industry in District Tangaran Sambas of Weast Kalimantan. This study aim to determine profit and feasibility of soybeans into tofu. The research method was the study conducted a census in distric Tangaran remember only has 3 Small Family Tofu process. Data analysis included analysis of cost, revenues, profits and efficiency such as R/C or BEP. The result showed: 1) The cost of procecing 616 kg soybeans is Rp. 4.541.307,- ; 2) Tofu (the BEP production) price is Rp. 177,21 per piece volume reaching 14.885 pieces with a size 4,5 cm x 4,5 cm per piece; 3) 1 kg soybean at Rp. 5.000,- obtain from the value added processing of soybeans into tofu is Rp. 8.455,-